Financing of women-owned small and medium enterprises in Malaysia / Ismail Ab. Wahab, Zarina Salleh and Laila Mohammad Kamaruddin (Faculty of Business and Management ; UiTM Press, 2005)
This paper presents findings of a research study designed to investigate the current financing practices and problems of women-owned small and medium enterprises (SMEs) in Malaysia. Despite the rapid expansion in the range of financial initiatives, there is a widespread perception that financing difficulties continue to exist and hinder the growth of women-owned SMEs. This study investigates the financing practices of women-owned SMEs and discusses the existence or otherwise of financing difficulties. Our empirical research shows that, in addition to personal savings of the entrepreneurs and the retained profits of the firms, the majority of women entrepreneurs in Malaysia use external sources to finance their businesses. However, the results also reveal that women-owned SMEs in this country still face difficulties in raising external finance. While a significant number of women entrepreneurs have been successful in their applications for external finance, the majority of them have problems financing their business operations and expansion. Notwithstanding the complexities, they normally manage to obtain a certain amount of funding, which is still insufficient to support working capital and expansion requirements.